GAMBARAN PENGETAHUAN WARGA TENTANG PENYAKIT TUBERKULOSIS DI LINGKUNGAN KELURAHAN PUTAT JAYA SURABAYA - Lataima, Nurmawati; Siagian, Martha Lowrani; Artini, Budi (Bahasa Indonesia, 2023)
Background, Tuberculosis is an infectious disease caused by Mycobacterium Tuberculosis, this disease is still a global public health problem. The source of infection is BTA (+) pulmonary tuberculosis sufferers who can infect people around them. Method, this research uses a descriptive design with a cross sectional approach. The population taken was the total of 39 participants in the Pulmonary Tuberculosis counseling in the Putat Jaya Surabaya Community Health Center working area, using a questionnaire. Data analysis used univariate analysis of frequency distribution. The research results showed that the number of participants present was 39 people, consisting of 6 (15%) men and 33 (85%) women. Before the counseling was carried out, there were 15 people (38%) with the criteria of lacking knowledge about TB, 14 people (36%) with sufficient criteria and 10 people (26%) with good criteria. Meanwhile, based on the data obtained after being given counseling, there was an increase in public knowledge regarding TB, namely 25 people (64%) had good knowledge, 9 people (23%) had good knowledge, and 5 people (13%) had insufficient criteria. In conclusion, there was an increase in knowledge after providing education about TB disease in the Putat Jaya Surabaya community